Terror in the mind of God the global rise of religious violence - Juergensmeyer, Mark 1940- (Comparative studies in religion and society, 2017)
"Completely revised and updated, this new edition of Terror in the Mind of God incorporates the events of September 11, 2001 into Mark Juergensmeyer's landmark study of religious terrorism. Juergensmeyer explores the 1993 World Trade Center explosion, Hamas suicide bombings, the Tokyo subway nerve gas attack, and the killing of abortion clinic doctors in the United States. His personal interviews with 1993 World Trade Center bomber Mahmud Abouhalima, Christian Right activist Mike Bray, Hamas leaders Sheik Yassin and Abdul Azis Rantisi, and Sikh political leader Simranjit Singh Mann, among others, take us into the mindset of those who perpetrate and support violence in the name of religion."...Provided by publisher